Manifestations of and factors influencing posttraumatic growth among Chinese Crohn’s disease patients: a qualitative exploration - Hong Li; Dandan Chen; Chen Zhang; Yunxian Zhou (International Journal of Qualitative Studies on Health & Well-Being, 2024)
Objective This qualitative study aims to explore the manifestations of posttraumatic growth among Chinese patients with Crohn’s disease from a cultural perspective and to identify the factors influencing it. Methods A descriptive qualitative research method was used. Semistructured interviews were conducted with 19 patients with Crohn’s disease from several hospitals in Hangzhou, Zhejiang Province, China, and the China Crohn’s and Colitis Foundation. Results There were five key manifestations of posttraumatic growth experienced by Chinese patients with Crohn’s disease: improving interpersonal relationships, enhancing personal strengths, changing life priorities, expanding possibilities and gaining religious faith. Posttraumatic growth among patients was predominantly influenced by individual factors, the disease condition and social support. Conclusion The findings regarding the manifestations of and factors influencing posttraumatic growth in Chinese patients with Crohn’s disease are consistent with those in previous studies in patients with chronic diseases. However, our study underscores the multifaceted impact of Chinese cultural characteristics on posttraumatic growth among Crohn’s disease patients. These findings can offer valuable guidance for future complex interventions and relevant clinical studies conducted within the Chinese population.